Improving Entrepreneurs' Digital Skills and Firms' Digital Competencies through Business Apps Training: A Study of Small Firms - Nick Drydakis (Global Labor Organization (GLO), 2022)
The lack of awareness of digital services and outcomes is a concern in business environments since small firms need to improve their digital competencies. The present exploratory study investigated whether business apps training was associated with entrepreneurs' and firms' digital advancements. The business apps training was offered to migrant entrepreneurs running small firms in Athens (Greece) over three months, with data collected before and after the training. The analysis revealed that business apps training was positively associated with entrepreneurs' attitudes toward technology, willingness to change (relating to technology/skills/operations), and internet/digital skills, as well as increased use of business apps. Moreover, the training was positively associated with firms' digital competencies related to communication, networking, social media, customer relationship management, payments, accounting and finance, and project management operations. Furthermore, the business apps training was positively associated with migrant entrepreneurs' integration into Greek society. Given the increased number of migrants in Europe, factors that positively impact their entrepreneurship and integration merit consideration. The study provides researchers with a systematic method for evaluating the association between business app training and entrepreneurs' and firms' digital advancements.
Keywords: M53; L26; O31; O33; 330; Training; Entrepreneurs; Small Firms; Business Apps; Digital Skills; Digital Competencies; Artificial Intelligence; Integration